2020
DOI: 10.3390/ijms21051768
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of RAD52, Its Prognostic Impact in Rectal Cancer and Association with Poor Survival of Patients

Abstract: The DNA damage response enables cells to survive and maintain genome integrity. RAD52 is a DNA-binding protein involved in the homologous recombination in DNA repair, and is important for the maintenance of tumour genome integrity. We investigated possible correlations between RAD52 expression and cancer survival and response to preoperative radiotherapy. RAD52 expression was examined in tumour samples from 179 patients who underwent surgery for rectal cancer, including a sub-cohort of 40 patients who were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 61 publications
0
15
0
1
Order By: Relevance
“…Several studies reported an association between high RAD52 expression level in tumor samples with poor patient prognosis and disease prognosis ( Jewell et al, 2010 ; Lieberman and You 2017 ; Ho et al, 2020 ). In a study of cancer cells containing an inactivated RECQL4 gene and upregulated RAD52, inhibition of RAD52 sensitized the cancer cells to ionizing radiation ( Kohzaki et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported an association between high RAD52 expression level in tumor samples with poor patient prognosis and disease prognosis ( Jewell et al, 2010 ; Lieberman and You 2017 ; Ho et al, 2020 ). In a study of cancer cells containing an inactivated RECQL4 gene and upregulated RAD52, inhibition of RAD52 sensitized the cancer cells to ionizing radiation ( Kohzaki et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…RAD52 promotes cell proliferation capacity and mobility in HCC [ 31 ]. Elevated RAD52 expression is related to worse DFS in patients with rectal cancer [ 32 ]. In this paper, we confirmed that the progression of OC cells was reduced dramatically after RAD52 knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…IL7 may play an anti-tumor role through apoptosis pathway [48]In addition, IL7 can also enhance the anti-tumor immunity by combining other factors to enhance the function of immune cells (46). The protein encoded by the RAD52 gene is a DNA-binding protein that participates in the DNA repair process, Double-strand breaks are the main cause of tumor cell death, and the RAD52 protein plays an important role in the repair of double-strand break damage (33,47). In addition, the RAD52 protein is also essential for DNA synthesis during mitosis (48).…”
Section: Discussionmentioning
confidence: 99%